Application and risk response of deep synthesis technology - Jingwen LI; Yawen LI (网络与信息安全学报)
Deep synthesis technology is a widely used application in the field of artificial intelligence, particularly in intelligent services, audio and video production, media communication and information services.A basic research was conducted on the principle and implementation of deep synthesis technology.And the application of deep synthesis technology were analyzed, such as robot writing, voice synthesis, intelligent customer service, voice replication, face synthesis, posture manipulation, virtual characters and virtual scenes.Based on the analysis of the characteristics and development trend of the application of deep synthesis, the risks brought by the application of deep synthesis technology were summarized, such as the generation and dissemination of false information, infringement of the legitimate rights and interests of others, utilization by other illegal and criminal activities, and impact on national security.The measures taken by the EU, United States and China to govern the application of deep synthesis technology were studied and the countermeasures were recommended such as building a comprehensive regulatory rule system, strengthening technical supervision, and improving risk prevention awareness across society.Furthermore, the need for intelligence, authenticity, and universality in the application of deep synthesis technology was highlighted.Based on the analysis of the characteristics and development trends of deep synthesis technology, a comprehensive insight into the potential risks and countermeasures associated with its application governance were provided.